Efficacy of recombinant adenovirus expressing G protein of rabies in mice (Revista de Educação Continuada em Medicina Veterinária e Zootecnia do CRMV-SP, 2013)
Since rabies case occurred again in 1993, a number of animal rabies had been reported up to 2011. Even though animal rabies cases seemed to be decreased, the continuous outbreak was identified at some counties of Gangwon Provinces of Korea. Although national mass vaccination program with live and inactivated vaccines to domestic and pet animals has blocked dog-to-dog transmission, most of rabies cases are related with to animal bitten by rabid raccoon dogs and rabies in wild animals are not eradicated. A safe and effective vaccine is needed for the immunization of wild animals and dogs. Human adenoviruses have been studied as viral vector. In this study, we constructed three kinds of recombinant adenovirus expressing rabies proteins and checked efficacy of the constructs in mice.